2018
DOI: 10.1371/journal.pone.0190618
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl peptidase 3, a novel protease from Leishmania braziliensis

Abstract: The increase of leishmaniasis cases worldwide and the emergence of Leishmania strains resistant to current treatments make necessary to find new therapeutic targets. Proteases are appealing drug targets because they play pivotal roles in facilitating parasite survival and promoting pathogenesis. Enzymes belonging to the dipeptidyl peptidase 3 (DPP3) group have been described in different organisms such as mammals, insects and yeast, in which these enzymes have been involved in both protein turnover and protect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…The statistically significant proteins (red filled circles at upper right portion of Fig. 3D ) preferentially synthesized by the parasite under severe Hsp90 inhibition include known virulence factors superoxide dismutase (SOD) ( 44 ), Hsp70 ( 45 ), and dipeptidyl peptidase 3 ( 46 ), important metabolic enzymes, and histone H4. Gene ontology (GO) analysis of the statistically significant upregulated proteins revealed unfolded protein binding ( P value, 3.77e −6 ) and protein folding ( P value, 2.53e −7 ) as significantly enriched molecular function and biological process GO terms, respectively ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The statistically significant proteins (red filled circles at upper right portion of Fig. 3D ) preferentially synthesized by the parasite under severe Hsp90 inhibition include known virulence factors superoxide dismutase (SOD) ( 44 ), Hsp70 ( 45 ), and dipeptidyl peptidase 3 ( 46 ), important metabolic enzymes, and histone H4. Gene ontology (GO) analysis of the statistically significant upregulated proteins revealed unfolded protein binding ( P value, 3.77e −6 ) and protein folding ( P value, 2.53e −7 ) as significantly enriched molecular function and biological process GO terms, respectively ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Differences were also observed in the prediction of the subcellular localizations of these proteins, which was based only on sequence properties by using a deep neural network provided by the DeepLoc-1 server. The accuracy of these analyses was assessed with three L. (V.) braziliensis proteins (two with RNA binding capacity (LbrM.25.2210 and LbrM.30.3080) [15], and dipeptidyl-peptidase 3 (LbrM.05.0940) [16], all of which have experimentally defined subcellular locations. The program accurately identified the cellular location of LbrM.25.2210 as the parasite nucleus (0.50) and LbrM.30.3080 and LbrM.05.0940 as the cytoplasm (0.85 and 0.97, respectively, data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Studies suggested the involvement of the human DPPIII protein in protein turn over, oxidative stress and pain modulation and inflammation [49]. In Leishmania, the protein was characterized in L. braziliensis demonstrating its role in parasite survival in the vector, or host environments through peptide degradation and thus use of amino acids for energy production in stressful environment [50]. Presence of this protein was demonstrated in the secretome of L. donovani, which classified it as a candidate virulence factor that might be part of a stress response of the parasite [51].…”
Section: Introductionmentioning
confidence: 99%
“…Presence of this protein was demonstrated in the secretome of L. donovani, which classified it as a candidate virulence factor that might be part of a stress response of the parasite [51]. A 2040bp DPPIII gene is present in all Leishmania and other trypanosomatids sequenced genomes [50]. However, the gene seemed absent in the Trypanosoma genus including T. brucei and T. cruzi species [50,52].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation